Factors and strategies to overcome low adoption of adjudication in Malaysia - Rasidi, Daniel Iskandar Sulaiman (2022)
Issues related to payment have long been known to exist in the construction industries all around the world. To tackle payment issues, each country has devised their own form of Security of Payment (SOP). Each form of Security of Payment from different countries are however not the same from one another. For Malaysia, a particular act had been gazetted back in the year of 2012 on the 22nd of June by the Ministry of Works. However, the act was only implemented three years later in 2015 on the 15th of April. This Security of Payment act is known as the Construction Industry Payment and Adjudication Act (CIPAA). Even though it has already been seven years since CIPAA established, the act and all its features are still relevantly new to the Malaysian construction industry players. The reason for this statement is that payment issue still exists even after the launch of CIPAA. In 2016, research was conducted to find the current statistic related to payment issues in Malaysian construction industries. It was later revealed that 91% of the respondent agreed that issues related to payment is still ongoing and is becoming a great burden in the industry. Not only that, but the same research also found that 81% of the payment issue are related to private projects while the other 19% are payment issues related to government projects (Abdul et al., 2016). This research has two objectives. The first objectives of the research are to determine the challenges that contractors face when dealing with late payment using CIPAA. The second objective is to determine ways to assist contractors that are dealing with payment issues through adjudication. The scope of this research will cover the responses of contractors in the Malaysian construction industries in relation to the use of the CIPAA as an instrument to tackle payment issues as well as the means to encourage and ease the contractor to adjudication. This research thesis is significant because, at the end of the research, the factor that causes the contractor and subcontractor to not use the Construction Industry Payment and Adjudication Act to tackle payment issues can be identified. Other than that, the ways to assist contractors that are dealing with payment issues through adjudication can also be identified so that they can be implemented in the real world of the Malaysian construction industry. This research will be separated into five phases in which will include initial analysis, literature review, collecting information and data, analyzing information and data, and finally discussion and conclusion. For the first objective, the method of collecting information and data will be by questionnaire. For the second objective, the method of collecting information and data will be by interviews. In conclusion, the challenges that contractors face when dealing with late payment using the Construction Industry Payment and Adjudication Act are related to the cost of adjudication itself. As for the second objective, assistance from legal personnel, lawyer or the AIAC make video tutorial related to adjudication, AIAC modifying the CIPAA form to be more user-friendly, and company hosting seminar related to CIPAA are some of the ways to assist contractors that are dealing with payment issues through adjudication.